(untitled) - Strachman, Daniel A. (Hoboken, N.J., 2009)
The Long and Short of Hedge Funds presents readers with a unique look at these investment vehicles, the people who run them, and those who provide services to them. This book is a detailed guide of the industry and offers rare access to hedge fund managers and industry participants. The book provides the reader with a real education about hedge funds, gaining a firm understanding of the industry
Keywords: Hedge funds,Nguồn quỹ dự phòng